Application of SDGS Programme to Economic Welfare and Growth in the Ganding Sub-District of the Sumenep District - Bimo Aryo Nugroho; Susy Muchtar (Budapest International Research and Critics University, 2023)
At the international level, Indonesia has made a very strong commitment to decent work and plays an important role in ensuring that employment and labour issues are included in the Sustainable Development Goals (SDGs). In Indonesia, labour and employment is still an interesting discussion, especially if it is associated with the demographic bonus which should have great potential and role in national economic development. To test and analyse how effective and efficient the implementation of the SDGs 8 Pillars of Economic Development, especially regarding welfare and economic growth in Ganding District, Sumenep Regency.This research uses an approach to analyse the role of government in good governance as seen from the implementation of SDGs and the issues and strategies applied. The subjects of this study were Sumenep district government agencies. Survey respondents were village heads in Ganding sub-district and local community leaders. This research was analysed using content analysis. Primary data was obtained from interviews and questionnaires distributed to village heads and village officials who responded. Based on the results of these interviews, the programmes carried out by the village government and the Ganding sub-district government in Sumenep district are very effective and efficient in achieving the sustainable goals in SDGs No 8 on Decent Work and Economic Growth. To improve innovation performance, village governments must be more proactive in responding to various issues related to changes in the regional environment both internally and externally. These changes must be responded wisely through research and development activities so that village tourism can maintain its existence in the future. One of the things that need to be considered is related to governance in the implementation of SDGs. To carry out the responsibilities of tourism villages in terms of management governance, the Village Government must become more innovative in product development, more effective and efficient ways of doing business, controlled resource utilisation, and the use of appropriate technology.